Estratégias “ômicas” para o estudo de marcadores moleculares da fertilidade: mapeamento das proteínas seminais com afinidade à gelatina e heparina de espécies domésticas e metaboloma dos espermatozoides bovinos - Santos, Fágner Cavalcante Patrocínio dos (2017)
Animal fertility is a factor that affects reproductive efficiency in herds and has a strong impact on the economy for meat and milk production. Thus, biotechnological tools such as a proteomic and metabolomic have been used and represent a potent tool for a choice of breeding with proven fertility for herds. Biomolecules such as gelatin-binding proteins (GBP) and heparin (HBP) and metabolites participate of several physiological events in the sperm cell until fertilization. Thus, these seminal biomolecules can serves as biomarkers for fertility in several species. Therefore, the objectives of the present study were (1) to identify the GBP and HBP profile in the seminal plasma of farm species and (2) to identify sperm metabolites associated with fertility in Holstein bulls. To achieve the objective of study 1 the seminal plasma of bovine, caprine, ovine, rabbit, equine and swine species were subjected to fast-performance liquid chromatography (FPLC) and mass spectrometry. In addition, bioinformatics tools were used to evaluate the physiological processes which these proteins are involved. The total GBP were in bovine (354), caprine (103), ovine (51), rabbit (146), equine (25) and swine (87) species. Among the most abundant GBP were identified proteins of spermadhesins. The total HBP were in bovine (894), caprine (789), ovine (647), rabbit (600), equine (556) and swine (86) species. The HBP with higher concentrations include bodhesin 2, protein S100, clusterin, PSP-I, PSP-II, among others. In silico analyzes shown that HBP mainly participate in cellular biological processes and have molecular binding function. To achieve the goal of study 2, the sperm metabolites of 10 bulls with high (n = 5) and low (n = 5) fertility were identified through GC-MS technique. In addition, multivariate and univariate statistical analyzes were performed through the MetaboAnalyst 3.0 program to identify metabolites associated with fertility. The results showed that among the 41 different metabolites identified in spermatozoa the levels of four compounds were significantly different and can be used as molecular biomarkers. These metabolites were aminomethane and azelaic acid (higher in spermatozoa of low fertility bulls) and butyric acid and urea (higher in spermatozoa of high fertility bulls). The results of this research are significant because they help to promote basic animal science and the proteins and metabolites identified can be used in reproductive biotechnology to evaluate the semen quality and predict reproductive fertility.